Improving Student Writing Skill in Descriptive Text by Using Recitation Method Through Picture Media - Permata S, Vania Sri; Hutagalung, Yohana; Tarigan, Sri Ninta; Siregar, Tiarnita Maria Sarjani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
The purpose of this research is to find out whether Picture Media by using Recitation Method can improve student’s descriptive text writing ability at nineth-grade Junior High School of SMP Masehi Medan. Research was conducted using action in the classroom. In two cycles, the action was study carried out. Open-ended questionnaires and instrument writing tests were used to analyze the data, along with both qualitative and quantitative methods. The results of this research indicate the students were able to come up with a variety of better methods to begin description when using picture media as a writing prompt. Additionally, the student could check that the right tense was utilized in their writing. Additionally, the students could expand their vocabulary to identify words.